Gazetteer of the Persian Gulf 'Omān, and Central Arabia - Lorimer, John Gordon (Gregg international publishers limited, 1970)
Don John C. Wilkinson (mars 2026)

Louis Massignon - Six, Jean-François (Éditions de l'Herne, 1970)
Keywords: Orientalisme – France

الفتاة الليبية ومشاكل الحياة - معمر, علي يحيى (دار الفتح‏, 1970)
Réédité en 2010 par Dhamiri avec le titre modifié.

تاريخ طرابلس الغرب - ناجي, محمود (كلية الآداب, 1970)
Keywords: Djebel Nefousa – Histoire

Bidaʿ al-Tafāsīr fī ‘l-Māḍī wa’l-Ḥāḍir - Naʿnāʿa, Ramzī (Wizārat al-Awqāf wa-Shu’ūn al-Muqaddasāt al-Islāmiyya, 1970)
Pp. 65-72: al-Ittijāh al-Munḥarif fī Tafsīr al-Khawārij
FMC

Ajwiba wa-Fatāwà - Muʿammar, ʿAlī Yahyā (Manshūrāt Dār al-Daʿwa, 1970)

Asās al-Ṭāʿāt (Manshūrāt Dār al-Daʿwa, 1970)

Kitāb al-Duʿā’ (Manshūrāt Dār al-Daʿwa, 1970)

ʿUmān wa-baʿḍ Juzur al-Muḥīṭ al-Hindī - Saʿdī, ʿAbbās Fāḍil al- (Ministry of Culture and Information, 1970)

Oman the modern state (Ministry of Information, 1970)
Keywords: Vie politique – Oman – 1970-2020

Sultanate of Muscat and Oman (1970)
Keywords: Vie politique – Oman – 1970-2020

‏وادي مزاب بلاد الكفاح: دراسة تاريخية اجتماعية تلقي أضواء على نشأت هذا البلد وحياة ساكنيه - طلاي, إبراهيم بن محمد (دار البعث, 1970)

Front Populaire de Libération du Golfe Arabique Occupé 1965-1970 (1970)
Keywords: Dhofar

Geschichte des arabischen Schrifttums : Medizin - Pharmazie - Zoologie - Tierheilkunde bis ca. 430 H. - Sezgin, Fuat (Brill, 1970)
Keywords: Bibliographie

al-Willūlī fī Fiqh al-ʿIbādāt - Zuwārī, ʿAbd al-Raḥmān b. Sulaymān al- (1970)
Keywords: Poésie religieuse – Zouara

A history of Zanzibar: a study in constitutional development, 1934-1964 - Ayani, Samuel G. (East African Literature Bureau, 1970)
Keywords: Zanzibar

Berbère de l'Oued-Mzab: le verbe, glossaire, classification - Dallet, Jean-Marie (Fichier de documentation berbère, 1970)
Keywords: Linguistique – Mzab

Le M'zab: architecture ibadite en Algérie - Roche, Manuelle (Arthaud, 1970)
Keywords: Architecture – Mzab

Musée des Arts et Traditions populaires de l’île de Djerba - Louis, André (Institut National d’Archéologie et d’Art, 1970)
Keywords: Musée – Djerba

Die Djerbi in Tunesien: soziologische Analyse einer nordafrikanischen Minderheit - Freund, Wolfgang Slim (Hain, 1970)

Arts traditionnels de Tunisie - Office national de l'artisanat Tunisien (Office National de l'Artisanat, 1970)
Keywords: Artisanat – Djerba

Khereddine, ministre réformateur (1873-1877) - Smida, Mongi (Maison tunisienne de l'édition, 1970)
Keywords: Famille Bin Ayyad